Cleidocranial dysplasia with spina bifida: case report - Khan, Mubeen; Puja, Rai (Archives of Oral Research, 2010)
OBJECTIVE: To present and discuss a case of a rare disease in a 35 year old otherwise healthy maleIndian in origin reported to the Department of Oral Medicine and Radiology of the Dental College andResearch Institute, Bangalore, India. DISCUSSION: The cleidocranial dysplasia is a rare disease whichcan occur either spontaneously (40%) or by an autosomal dominant inheritance. The dentists are, mostof the times, the first professionals who patients look for to solve their problem, since there is a delayin the eruption and /or absence of permanent teeth. In the present case multiple missing teeth was thereason for patient’s visit to odontologist. CONCLUSION: An early diagnosis allows proper orientationfor the treatment, offering a better life quality for the patient.